Methodology of Risk Management Associated with Short Life Cycle Business Opportunities - Pawel KROLAS (Communications of International Proceedings, 2020)
The environment may have a negative, neutral or positive influence on the organization. The unpredictability of the negative and neutral environment is often a source of potential threats whereas positive conditions creates opportunities to the organization. The turbulent environment of the enterprise forces on managers to take action dealing with the use of the business opportunities with limited possibility of risk verification. It is connected with short life cycle business opportunity and the dynamic nature of the risk.  The paper presents meaning of the business opportunity and the risk connected with the use of the opportunity for the organizations.  Based on different case studies the risk management process based on use of life cycle bossiness opportunity was created. The elaborated methodology allows evaluating of risk factors connected with the business opportunity from different sectors.
Keywords: Risk; Risk Management; Risk Management Process; Opportunity; Life Cycle